Brown bear reintroduction in the Southern Alps: to what extent are the expectation being met? - Tosi, Guido; Zibordi, Filippo; Mustoni, Andrea; Giovannini, Ruggero; Groff, Claudio; Zanin, Maurizio; CHIRICHELLA, Roberta; APOLLONIO, Marco (Journal for Nature Conservation, 2015)
tLarge carnivores, such as brown bears (Ursus arctos), are flagship species for the conservation of biodi-versity and their reintroduction represents a strong challenge. However, the results of reintroductionshave only recently been documented in the literature. Given the global decline of large carnivores, docu-menting the results of such attempts is crucial for future conservation management. Here we examinedthe reintroduction of brown bears into the Italian Alps. The majority of bears released (10 individuals)adapted well to the release area and this resulted in the increase of the brown bear population. At theend of 2012, the area with a stable presence of females was around 1250 km2(minimum density = 3bear/100 km2). Between 2002 and 2012, 34 reproductive events occurred and a total of 74 cubs wereborn, thus reaching a minimum population size of 47 individuals. No less than 21 young males dispersedinto adjacent Italian regions or into other countries, such as Switzerland, Austria, and Germany. However,despite a high mortality rate and at least two cases of illegal killing reported in the last 2 years (2013 and2014), a remarkable population growth rate (current level of 15.6%) has been observed.The damages correlated with bear population size (F = 17.922, p < 0.01) were primarily inflicted onbeehives (39%) and livestock (26%), with an economic relevance of D 41,374 per year for compensationand D 23,527 per year for prevention. The only case of injury to humans ever since the beginning of theproject was recorded in 2014, when a female defending her two cubs inflicted minor physical injuries to aman. And yet, public opinion changed radically, from a widespread acceptance of bears at the beginning ofthe project to an opposition to their presence, the increase of their population, and the new translocationsaiming at replacing problem bears that had previously been removed. According to the present trend, thepopulation may reach a range of 60–94 individuals in 2017. Therefore, a proper management of ...